Genetic structure of wildcat (Felis silvestris) populations in Italy. Issue 8 (22nd June 2013) - Mattucci, F.; Oliveira, R.; Bizzarri, L.; Vercillo, F.; Anile, S.; Ragni, B.; Lapini, L.; Sforzi, A.; Alves, P. C.; Lyons, L. A.; Randi, E.
Abstract Severe climatic changes during the Pleistocene shaped the distributions of temperate‐adapted species. These species survived glaciations in classical southern refuges with more temperate climates, as well as in western and eastern peripheral Alpine temperate areas. We hypothesized that the European wildcat (Felis silvestris silvestris) populations currently distributed in Italy differentiated in, and expanded from two distinct glacial refuges, located in the southern Apennines and at the periphery of the eastern Alps. This hypothesis was tested by genotyping 235 presumed European wildcats using a panel of 35 domestic cat‐derived microsatellites. To provide support and controls for the analyses, 17 know wildcat x domestic cat hybrids and 17 Sardinian wildcats (F. s. libyca) were included. Results of Bayesian clustering and landscape genetic analyses showed that European wildcats in Italy are genetically subdivided into three well‐defined clusters corresponding to populations sampled in: (1) the eastern Alps, (2) the peninsular Apennines, and (3) the island of Sicily. Furthermore, the peninsular cluster is split into two subpopulations distributed on the eastern (Apennine mountains and hills) and western (Maremma hills and lowlands) sides of the Apennine ridge. Simulations indicated Alpine, peninsular, and Sicilian wildcats were isolated during the Last Glacial Maximum. Population subdivision in the peninsula cluster of central Italy arose as consequence of a more recent expansions of historically or ecologically distinct European wildcat subpopulations associated with distinct the Continental or Mediterranean habitats. This study identifies previously unknown European wildcat conservation units and supports a deep phylogeographical history for Italian wildcats.